Pengalaman Siswa Kelas VIII dalam Berkomunikasi Bahasa Indonesia Ditinjau dari Kepercayaan Diri di SMPN 23 Medan - Helda Emeninta Br Bangun; Sonia Septiani Br Sembiring; Ardina Tridewi; Nita Salsabila Br Tarigan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the experiences of eighth-grade students at SMP Negeri 23 Medan in communicating using formal Indonesian language viewed from the aspect of self-confidence. This research is motivated by the phenomenon of students’ low confidence in speaking formal Indonesian in the school environment, especially during presentations, answering teachers’ questions, and expressing opinions in front of the class. Many students experience nervousness, fear of making mistakes, lack of self-confidence, and difficulty arranging words when speaking formally. This study employed a descriptive qualitative approach with data collection techniques through in-depth interviews involving six eighth-grade students of SMP Negeri 23 Medan. The data were analyzed using the interactive model of Miles and Huberman through the stages of data reduction, data presentation, and conclusion drawing. The findings revealed that self-confidence has a significant influence on students’ communication fluency. Students with low self-confidence tend to experience communication anxiety, speak hesitantly, lose focus, and choose to remain silent when speaking in front of the class. In addition, the peer environment also influences students’ courage in using formal Indonesian, where ridicule and negative responses make students feel embarrassed and afraid to speak. On the other hand, support from teachers, friends, and regular speaking practice opportunities can help students improve their confidence and communication skills. This research is expected to serve as a reference for Guidance and Counseling teachers in designing services focused on developing students’ self-confidence and communication skills at school.